Poliandri di Kalangan Masyarakat Muslim: Studi Sosiologis di Kelurahan Bunut Kecamatan Kisaran Barat Kabupaten Asahan - Lubis, Hasliza (Institut Agama Islam Negeri Curup, 2020)
The purpose of this research is to know the factors that cause the Muslims in Bunut village west Kisaran District Asahan Regency to do polyandry practice. The process of a wife’s marriage is still valid marriage to her first husband. Wives get married to other man without any divorced or divorce proceedings because the wife is separated form the first husband. This research is a field study, researchers use qualitative debitor that use the interview method as primary data which then generates descriptive analytical data. Results of this research, after conducting the factors are influenced by economic factors, low levels of education, and lack of awareness of people's understanding of the law, the first husband is not responsible, the husband's work away from his wife, polygamy husband, high lust, and weak supervision of the Office of Religious Affairs (KUA) when the parties get married husband and wife. Regarding public awareness in Bunut about marriage belong is low so that they does not follow the rules in Islamic law, marriage law and compilation of Islamic law.